How Responsible Leadership and Knowledge Sharing Foster Work Engagement: The Moderating Role of Job Tenure in a Regional Bank - Egi Andiyana; Nicqi Airul Hernawan; Satrias Djamaran; Toni Suhara (PINISI Discretion Review, 2026)
Work engagement is strategically important for service quality, adaptability, and sustainable performance in banking organizations. Although responsible leadership and knowledge sharing have each been associated with favorable employee outcomes, limited evidence explains their simultaneous influence on engagement and the conditions under which these relationships become stronger in regional government-owned banks. This study examines the effects of responsible leadership and knowledge sharing on work engagement and tests job tenure as a moderator. A quantitative, cross-sectional survey was conducted among 127 permanent employees of a regional government-owned banking institution in Tangerang Regency, Indonesia. Respondents were selected through purposive sampling, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM) in SmartPLS 3. The results show that responsible leadership has a positive effect on work engagement (β = 0.643, t = 13.209, p < 0.001), as does knowledge sharing (β = 0.455, t = 9.412, p < 0.001). Job tenure strengthens both the responsible leadership–work engagement relationship (β = 0.174, t = 2.906, p = 0.004) and the knowledge sharing–work engagement relationship (β = 0.155, t = 2.554, p = 0.011). The model explains 75.3% of the variance in work engagement. The findings extend social exchange reasoning by identifying job tenure as a boundary condition that intensifies employees’ reciprocal responses to responsible leadership and knowledge sharing. For regional banks, the results underline the value of ethical and stakeholder-conscious leadership, systematic knowledge-sharing practices, and tenure-sensitive human resource interventions.